Comparison of 4.5% Versus 8% Sevoflurane for Inhalational Induction in Adults - Afroza Sardar, Muhammad Azam, Aamir Bashir, Ali Rehman, Mehreen Akram (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Inhalational induction is a frequently used anesthetic technique in pediatric patients. However, it is less frequently used in adult patients undergoing surgery. General anesthesia can be induced either by intravenous injection or inhalation of anesthetic drugs. There are no established guidelines about the usage of 4.5% vs 8% sevoflurane for inhalation induction in adults undergoing elective day care surgery. Aim: To compare mean time to loss of eyelash reflex using 4.5% vs 8% sevoflurane for inhalational induction in adult patients undergoing elective day care surgery. Methodology: This randomized controlled trial was conducted in the department of anesthesia, Mayo Hospital Lahoreover a period of six months from June 2018 to December 2018. A total of 60 patients were enrolled in the study. We included adult patients aged 18-60 years of either gender and ASA status I & II undergoing elective day care surgery. While, patients having history of adverse reaction to inhalational agents and those who were on chronic sedatives, antipsychotic treatment were excluded. Demographic data of age and gender were obtained along with their body weight, height and BMI. They were randomly divided into two study groups using lottery method. After routine pre-op check and attaching standard anesthesia monitoring, patients in group-A and group-B were given 4.5% sevoflurane & 8% sevoflurane respectively at a fresh gas flow of 8 L/min of oxygen and they were instructed to take deep breaths while inhaling gas with help of face mask. Results: The mean age in 4.5% sevoflurane group was 42.27±11.83 years while in 8% sevoflurane group it was 45.43±12.76 years. In 4.5% sevoflurane group there were 12(40%) male and 18(60%) female cases while in 8% sevoflurane group there were 11(36.67%) male and 19(63.33%) female cases. The mean time to loss of eyelash reflex in 4.5% sevoflurane group was 88.57±6.71 seconds and in 8% sevoflurane group the mean time to loss eyelashes reflex was 67.87±5.90 seconds. The mean time to loss eyelashes reflex was statistically less in 8% sevoflurane group, with p-value 0.001. Conclusion: We concluded that mean time to loss eyelashes reflex was considerably lesser with8% sevoflurane when compared with 4.5% sevoflurane for inhalational induction in adult patients for elective day care surgery. Keywords: Inhalational induction, sevoflurane, eyelash reflex, day care surgery.